Antioxidant and antimicrobial potential of Delphinium denudatum Wall. Evaluated by validated high-performance thin-layer chromatography and in vitro assays (Kuwait Journal of Science)
Delphinium is a plant with healing properties that can be viewed as a natural source of antioxidants. This study was conducted to investigate the potential benefits of Delphinium denudatum root methanolic extract (DDRME) in biomedical research and antioxidant therapy by examining its effects and mechanisms of action in protecting cell growth from free radical damage. D. denudatum root methanolic extract was evaluated using densitometric high performance thin layer chromatography (HPTLC) to measure the amount of biomarker antioxidant candidate. Quercetin, a bioactive compound also known as 2-(3,4-dihydroxyphenyl)-3,5,7-trihydroxychromen-4-one, was isolated on silica gel 60F254 aluminum plates (500–4000 ngspot−1; r2 = 0.992 ± 0.0002; Rf:0.48 ± 0.02) at a wavelength of 254 nm. The antioxidant capabilities were assessed by in vitro antioxidant assay through testing the inhibitory concentration (IC50) for nitric oxide (NO), hydroxyl radical (OH), ferric reducing antioxidant power (FRAP), and superoxide radical scavenging (SO2.-), in addition to examining antimicrobial activity. Quantitative analysis indicated that DDRME contained high levels of phenolics, flavonoids, and total antioxidant capacity, leading to a significant inhibition of the produced free radicals. The ferric reducing antioxidant power (FRAP) assay showed higher antioxidant potential compared to other assays, indicating a strong correlation (r2 = 0.978) between bioactive components and antioxidant capabilities. D. denudatum root methanolic extract (DDRME) has the potential to be used as an eco-friendly medication to defend humans from microbial diseases, as polyphenolics effectively hinder the capability of microbes by increasing antioxidant enzyme function. © 2024 The Author